Structural transformation and labor market dynamics in Afghanistan: An evidence-based analysis of economic development and employment changes (2017–2024) - Pooya, Abdul Ahmad (Journal of Economics and Business Letters, 2025)
This study examines the path of structural change and the labor market in Afghanistan between 2017 and 2024, focusing on the disruption following the 2021 political transition. The analysis based on cross-sectoral data from the World Bank, the ILO, and national reports reveals a trend of "reversed structural transformation" when labor moves out of higher-productivity (services and manufacturing) sectors towards lower-productivity (agriculture and informal activities) sectors. Formal job destruction, the reduction of aid-funded services, and the massive return of Afghan migrants from Iran and Pakistan have all changed the employment structure, leading to an increase in unemployment, informality, and gender inequality. Despite a slight recovery in the agricultural, mining, and construction sectors, the economy remains vulnerable to external shocks and institutional inefficiencies. The results highlight that discovering the post-2021 labor adjustment in Afghanistan has been more of subsistence survival rather than productive relocation efforts and indicate the pressing need to have inclusive and employment-based recovery efforts.